PELATIHAN SISTEM INFROMASI GEOGRAFI KEPADA GURU SMA/MA SE-EKS KARESIDENAN SURAKARTA - Sunarhadi, Mohammad Amin; Dilahur, Dilahur; Priyono, Priyono (Universitas Muhammadiyah Surakarta, 2007)
The training aims at improving the capability of the trainingparticipants â teachers â for teaching Geography Information System by(1) giving information and introduction about the process in implementingSIG for the teachers of senior high schools (SMA/MA). (2) Demonstratinghow to operate the technology of geography information system and (3)socializing the existence and technological implementation system ofSIG. the methods used are speech, discussion, peer teaching and practice.The place to practice it is in the laboratory of Geography faculty of UMS.The participants are allowed to operate hardware and software of SIG.The result of pretest by using questioner and brainstorming shows thatmost of the participants master SIG in cognitive domain in comprehensionlevel for the theory of SIG, while for its operation; they are in perceptionlevel of psychomotor domain. At the end of the training, the participantsshow that there is the change of comprehension about the theory of SIGfrom cognitive level to implementation level, whereas in the operation ofSIG, the change is from perception level to implementation with guidance.The result of training is supplemented by the response of the participantswhich is appropriate to the target score. The response of the task ofidentification is the use of map and SIG in teaching Geography whichfinds that teaching Geography in senior high schools (SMA/MA) isdirected to 3 targets: 1. analyzing the impulse of physical nature and thedevelopment of the shape of the earth and its reservation. 2. Evaluatingsocial impulse in the earth and its interaction as well as its effect to ourlife and 3. Using the concept of region and graphic in understandinglocation, design, distribution and the relationship among the objectsinvolved the specification for industry.